Investigating The Level Of Emotional Intelligence Among Adolescents Of Secondary School (Journal of Namibian Studies : History Politics Culture, 2023)
The participants in this study were 85 high school seniors. An easy way to choose a sample was used. Mean, percentage, and standard deviation were used for statistical analysis. Teens attending public schools tend to have lower levels of emotional intelligence than their private school counterparts, according to the mean value result. When looking at the whole sample, there is a statistically significant difference in the emotional intelligence of male and female teenagers. The emotional intelligence of teenage girls was found to be higher on average. According to the study, emotional intelligence is defined as the ability to not only be aware of, but also to control and direct one's own emotions and those of other people. To further understand EI in teenagers, the research breaks it down into its component parts, which include things like self-awareness, self-regulation, social awareness, and relationship management. By using well-established EI assessment instruments, quantitative studies show that there are relationships between EI scores and academic accomplishments, demonstrating how EI influences the educational process. To get a better understanding of the emotional experiences of teenagers, qualitative research methods like interviews may reveal personal stories and difficulties they've encountered.